HOW TO IMPROVE YOUR READING AND WRITING - Eshmuradova Shahlo; Eldorbek Khamitov (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT:    This  article  provides  a  comprehensive  overview  of  practical methods and strategies to improve reading and writing skills effectively. It explores various reading techniques such as active reading, skimming, and scanning to enhance comprehension and retention of information. Additionally, it highlights the importance of building a strong vocabulary and understanding grammar to improve writing clarity and  coherence.  The  article  also  stresses  the  value  of  consistent  practice,  including writing regularly and seeking constructive feedback to identify areas for improvement. By addressing common challenges faced by learners, such as difficulty in organizing ideas  or  understanding  complex  texts,  this  article  aims  to  equip  readers  with  the necessary  tools  to  become  more  confident  and  proficient  readers  and  writers. Ultimately,  it  encourages  a  balanced  approach  that  combines  reading  widely  with deliberate writing practice to foster overall language development.